The Role of Ultrasonography in the Process of Weaning from Mechanical Ventilation in Critically Ill Patients - Lou’i Al-Husinat; Basil Jouryyeh; Ahlam Rawashdeh; Chiara Robba; Pedro Leme Silva; Patricia Rieken Macedo Rocco; Denise Battaglini (Diagnostics, 2024)
Weaning patients from mechanical ventilation (MV) is a complex process that may result in either success or failure. The use of ultrasound at the bedside to assess organs may help to identify the underlying mechanisms that could lead to weaning failure and enable proactive measures to minimize extubation failure. Moreover, ultrasound could be used to accurately identify pulmonary diseases, which may be responsive to respiratory physiotherapy, as well as monitor the effectiveness of physiotherapists’ interventions. This article provides a comprehensive review of the role of ultrasonography during the weaning process in critically ill patients.